3 × 3x = 9x
3 × y = 3y (but when added, that part gets eliminated)
3 × 3 = 9
So you end up with
9x + 3y = 9
x - 3y = -2
10x = 7
So your answer is B. 10x = 7. I hope this helps!
B. 10x = 7
x=7/10, you could work backwards to find y if it asked
Top row 6x+3y= 9
The correct option is (B)
Step-by-step explanation: The given equations are :
We are to select the correct result if the first equation is multiplied by 3 and then added to the second equation.
Now, multiplying equation (i) by 3, we get
adding equation (iii) to equation (ii), we get
Thus, the required result is
Option (B) is CORRECT.
b. hope this helps
Option B is correct.
The result is, 10x=7
Given the system of equation:
As per the statement: If the first equation is multiplied by 3 and then the equations are added.
Multiply equation  by 3 on both sides, we get
Using distributive property:
Now, add equation  and , to eliminate y we get;
Therefore, if the first equation is multiplied by 3 and then the equations are added, the result is, 10x = 7
multiplying the first equation by 3 gets us 9x+3y=9. basically multiplying each term by 3. now just do the same thing from the first part, so start with the new 9x+x and continue
rx and sx
(0,-3) see attached graph
a. to solve the system, graph the two equations.
x = y+3 becomes y=x-3 has m=1/1 and b=-3. start at (0,-3) on the y-axis and plot a point. then move up 1 unit and 1 unit to the right. plot a point and connect.
y=-4x+3 has m =-4/1 and b=-3. start at (0,-3) on the y-axis and plot a point. then move down four units and to the right 1 unit. plot a point and connect.
the solution is the point (x,y) where the two lines intersect. by the graph below it is (0,-3).
b. to solve by substitution, substitute y = -4x-3 into x= y+3
x= (-4x-3) +3
now substitute x = 0 back in to find y.
solution is (0,-3)
c. use elimination by adding the equations together.
then substitute into one equation to find y.